The origins of the Jimmy Savile scandal. Issue 1 (12th March 2018) - Smith, Mark; Burnett, Ros
Abstract : Purpose: The purpose of this paper is to explore the origins of the Jimmy Savile Scandal in which the former BBC entertainer was accused of a series of sexual offences after his death in 2011. The case has had a massive impact on UK policing and criminal justice policy and on care work, with implications for due process and public expenditure in responding to reports of sexual abuse. Design/methodology/approach: The paper draws on an Economic and Social Research Council funded project to collate data on the Savile case. It is based, primarily, on interview material from former pupils and staff members from Duncroft School, from whence initial allegations against Savile emanate, contrasting these with media accounts. Findings: The research provides a very different picture of Duncroft and the contemporary policy context to that presented in media accounts. A questioning account of the origins of the scandal emerges. The findings may lend themselves to a moral panics analysis but also point to the power of dominant stories in influencing public policy. Research limitations/implications: This paper is based on only a very small sample of interviews. The material is ethically sensitive in that it may be claimed or used to cast doubt on accounts of abuse. Social implications: The implications of the wider project from which it draws are potentially profound, casting doubt on the origins and detail of the Savile scandal. Originality/value: The paper addresses one of the major socio-cultural episodes in recent British history, which has had a profound effect on the workings of the criminal justice system, signalling a shift away from a presumption of innocence. It also offers insight into the cultural context of care work and the possibility, especially for males, of being subject to allegations made against them.